COLLEGE STUDENT CAREER DECISION MAKING: A LITERATURE STUDY - Bisinglasi, Clarissa Maldini Henderina; Maharani, Elviana Rizky; Wetangterah, Laetitia Nazaretha; Letelay, Sarah Marchella; Rambadeta, Maruel Djawa; Mage, Mernon Yerlinda Carlista (Journal of Health and Behavioral Science, 2025)
Throughout life, individuals face many important choices, including career decisions. This is a crucial stage for students in the transition to the world of work. This systematic literature review examines the factors that influence students' career decision-making using the PRISMA framework in empirical articles between 2015 and 2025; from 320 initial articles, 8 relevant studies were selected. The main findings show that self-efficacy, self-understanding, emotional intelligence, parenting, career counseling, and social support (family and friends) play an important role in improving students' ability to make career decisions. Practical implications highlight the need for self-development programs and career guidance services in higher education to improve students' career readiness.